A Pedagogy of the Parochial: Pedagogical Imperialism and Mutual Accompaniment in Christian Higher Education. Issue 1 (1st January 2019) - Jones, Alexander H.; Huff, James; Kellums Baraka, Mandy; Meitzner Yoder, Laura S.
Abstract: Historically, many North American educational engagements abroad have been entangled with colonialist logics that objectify and oppress those who live in Asia, Africa, Latin America, the Middle East, and Eastern Europe (Ogden, 2008 ). How does contemporary Christian higher education (CHE) programming such as study abroad and international engagement navigate the history of colonialism with present desires to expand and grow into international territories? This article explores this question through the theme of mutual accompaniment, resulting from a study of more than 250 interviews that students from a U.S. college on study abroad conducted with Majority World church pastors or other congregational leaders in communities where students lived. Interviews included a series of nine questions, including, "What would you like to say to the church in North America or the West?" Church leader responses pointed to the concept of mutual accompaniment we explore in this paper. After briefly delineating this concept, the article explores various ways CHE rationalizes its global engagements, highlighting especially the metaphor of cosmopolitanism. The ancient idea of a world citizen used today needs further articulation and analysis within CHE because of how the term can be conflated with practices of consumption and appropriation. Alternatively, as we explore in the concluding section, CHE can seek to advance a critical global citizenship with practices and habits that foster intercultural humility of the world citizen. By unraveling the colonialist logics embedded in cosmopolitanism, the article invites readers to consider how CHE students and programs can construct our positionality through embodied practices, in what we call "a pedagogy of the parochial."